EFFECT OF HALLOYSITE NANOTUBES ON THE MECHANICAL, PHYSICAL AND THERMAL PROPERTIES OF IMPACT MODIFIED POLY(LACTIC ACID) - Ang Hock Tee; Zainoha Zakaria; Muhammad Akmal Ahmad Saidi; Azman Hassan (PERINTIS eJournal, 2021)
Halloysite nanotubes (HNT) has gained much attention for research due to its reinforcing effect in mechanical properties, thermal stability, and nucleating effect. In this study, poly(lactic acid)/core-shell rubber/halloysite nanotubes (PLA/CSR/HNT) nanocomposites were prepared through melt blending, followed by compression molding and cut into different test specimens according to ASTM standards. The incorporation of HNT was performed at different content (0.5, 1.0, 1.5 and 2.0 phr) to study the effect of HNT content on mechanical, physical and thermal properties of impact modified PLA (PLA/CSR). It was found that the flexural strength of impact modified PLA improved significantly by 26.3% when 1.0 phr of HNT was incorporated while the flexural modulus recorded the highest reading at 1955 MPa by the incorporation of 0.5 phr HNT. The results revealed that agglomeration caused by higher content of HNT decreased the flexural properties of PLA/CSR/HNT compared to PLA/CSR. The water absorption and biodegradability of PLA/CSR/HNT were improved, primarily due to the hydrophilic nature of HNT which promoted the interaction with water molecules. From TGA results, 2.0 phr HNT was reported to greatly improve the thermal stability of PLA/CSR/HNT by a higher shift of degradation temperature. Based on DSC thermograms, a decline in the degree of crystallinity of PLA/CSR/HNT was observed when HNT was incorporated which could be due to inhibition of crystallization by HNT in PLA/CSR/HNT nanocomposites. In conclusion, incorporation of HNT at low content into impact modified PLA showed appreciable improvement in the mechanical, physical, and thermal properties of impact modified PLA.